Distance Testing on Point To Point Communication with Lora Based on RSSI and Log Normal Shadowing Model - Budi, Bloko; Machdi, Agustini Rodiah (Journal of Energy and Electrical Engineering, 2024)
Big cities are currently implementing the smart city concept, where Internet of Things (IoT) sensors are placed on the roads, then the data is collected and processed by smart devices to solve urban problems. IoT implementation is suitable using LoRa technology. In this paper, distance testing is carried out on point to point communications with LoRa in urban areas at a frequency of 915 MHz. The RSSI (Received Signal Strength Indicator) parameter value is what is observed, and the log normal shadowing model is used to compare the RSSI values computationally. The test results for the farthest distance were 3.37 km with an RSSI value of -104.5 dBm. The error value between the measured and calculated RSSI values is 7.3% where a path loss exponent (n) of 1.6 from the measurement results.